PEMANFAATAN LEARNING MANAGEMENT SYSTEM (LMS) DALAM PEMBELAJARAN DI SEKOLAH MENENGAH ATAS - Muh. Aidil; Febi Astriananta; Suci Rahmadani; Ade Ananda; Martita Dewi; Nurlindah; Maslang; Sarima Nur Sani; Sulistiawati; Muh.Muqtadir Alwah; Irna Fitriana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The COVID-19 pandemic accelerated the adoption of Learning Management Systems (LMS) in senior high school education. This study examines the utilization of LMS by focusing on students’ digital technology usage profiles, implementation effectiveness, as well as challenges and development strategies. Data from Statistics Indonesia (2025) indicate that mobile phone ownership among senior high school students reached 97.83%, while internet access reached 97.47%, providing strong support for LMS implementation in learning activities. Empirical studies demonstrate the effectiveness of LMS in improving learning outcomes. Hidayat (2025) reported an increase in knowledge scores from 71.50 to 90.58 and learning interest from 32.27 to 72.23 following the implementation of a Moodle-based LMS. Furthermore, Hodijah, Lestari, and Djeni (2025) found that the Sevima Edlink LMS significantly enhanced students’ learning independence and mathematical creative thinking skills. However, LMS implementation still faces several challenges, including disparities in digital infrastructure across regions, limited teachers’ digital competencies, and insufficient student learning autonomy. Therefore, a balanced hybrid learning model is considered the most suitable approach for the Indonesian context, supported by adaptive LMS development, teacher capacity building, active learning integration, and the use of learning analytics. In the future, the integration of Artificial Intelligence (AI) and platform interoperability has the potential to create more personalized, effective, and integrated learning experiences.